2010
DOI: 10.1021/jp1057786
|View full text |Cite
|
Sign up to set email alerts
|

Flowing versus Static Conditions for Measuring Multiple Exciton Generation in PbSe Quantum Dots

Abstract: Recent reports question the validity of pulsed fs-laser experiments for measuring the photon-to-exciton quantum yields (QYs) that result from multiple exciton generation (MEG). The repetitive nature of these experiments opens up an alternative relaxation pathway that may produce artificially high results. We present transient-absorption (TA) data for 4.6 and 6.6 nm diameter PbSe quantum dots (QDs) at a variety of pump photon energies. The data are collected under laminar flow conditions with volumetric flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
132
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 50 publications
14
132
1
Order By: Relevance
“…Here, s is found to be around 2.2 for lead-based QDs. e study by Midgett et al [28] and Mihaylov et al [38] in agreement with previous relevant literature also reports on properties for a variety of PbS x Se 1−x alloy QDs, with varying composition and radius, allowing one to draw conclusions about the size dependence of η for the di erent compositions of QDs ( Figure 6). It is suggested that higher MEG might be achievable in nonspherical crystal structures, although more data need to be collected to explore such con gurations.…”
Section: Pbx Quantum Dotssupporting
confidence: 89%
See 1 more Smart Citation
“…Here, s is found to be around 2.2 for lead-based QDs. e study by Midgett et al [28] and Mihaylov et al [38] in agreement with previous relevant literature also reports on properties for a variety of PbS x Se 1−x alloy QDs, with varying composition and radius, allowing one to draw conclusions about the size dependence of η for the di erent compositions of QDs ( Figure 6). It is suggested that higher MEG might be achievable in nonspherical crystal structures, although more data need to be collected to explore such con gurations.…”
Section: Pbx Quantum Dotssupporting
confidence: 89%
“…is gives a deceptive MEG-like signature in the spectroscopic data. Subsequently, it was found that this effect could be nullified simply by stirring the sample solution [28]. Another hurdle in the assessment of QYs for specific structures is clearly the large number of variables involved and relevant to these effects, such as the size, composition, shape, and method of observation.…”
Section: Multiple Exciton Generationmentioning
confidence: 99%
“…This is an advantage of exciting hot carriers that interact only weakly; these assumptions of the Auger analysis do not hold for band edge excitation of excitons. A likely explanation for the discrepancies in Figure 2 is charge ejection from the dot into a surface or ligand trap [6,7]. Charge separated dots have an emission lifetime of ~300 ps; the signal at 1 ns can be explained by assuming charge separation in ~4/5 of the dots at <Neh> = 10.…”
Section: Resultsmentioning
confidence: 96%
“…Whilst MEG has been detected in a number of materials, including silicon [57][58][59], most studies focused on QDs consisting of lead chalcogenides (PbS, PbSe and PbTe) [26,41,[60][61][62]. The large Bohr radius of lead chalcogenides, relative to, for example, silicon or GaAs [59,63,64], allows strong quantum confinement effects and efficient tuning of the confinement to produce a band gap in the near-IR region (0.7-1.0 eV) [65].…”
Section: Qd Materials For Meg In Pv Devicesmentioning
confidence: 99%
“…Such effects have led to difficulties in measuring MEG rates: a trapped charge may stay on a QD, which upon re-excitation by a subsequent pulse, may form a trion species that can be mistakenly interpreted as an MEG signal thereby complicating spectroscopic studies [43]. In solution-based measurements stirring the sample or the use of a flow cell prevents the same set of QDs being excited by consecutive pulses [61]. In films, however, it remains challenging to isolate effects that influence the MEG process itself, its measurement or the extraction of the generated charges.…”
Section: Impacts Of the Qd Surface On Meg In A Device Environmentmentioning
confidence: 99%